2018
DOI: 10.1111/desc.12725
|View full text |Cite
|
Sign up to set email alerts
|

An intervention that increases parental sensitivity in families referred to Child Protective Services also changes toddlers’ parasympathetic regulation

Abstract: Experiencing maltreatment in early childhood predicts poor parasympathetic regulation, characterized by low baseline parasympathetic activity and strong withdrawal of parasympathetic influence in response to tasks. The Promoting First Relationships (PFR) program improves parental sensitivity toward young children in families identified as maltreating. Using a subsample from a randomized control trial, we examined whether parental participation in PFR had lasting effects on toddlers' parasympathetic regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…The modality of delivery also matters. Emotion inductions that use film clips often result in increases in RSA (Alkon et al, ; Davis et al, ; Hastings, Klimes‐Dougan, Kendziora, Brand, & Zahn‐Waxler, ; Quigley & Stifter, ), which contrasts with patterns observed during naturalistic inductions (like an impossible or frustrating task), which often elicit physiological arousal (Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, ; Hastings et al, ; Perry, Calkins, Nelson, Leerkes, & Marcovitch, ). Using measures of RSA across four emotion contexts, Gaztke‐Kopp and Ram () showed that emotion context‐level physiological change explained a small but unique proportion of the variance in children's RSA scores.…”
Section: Temporally Moderate Contexts Of the Psychobiology Of Self‐rementioning
confidence: 99%
“…The modality of delivery also matters. Emotion inductions that use film clips often result in increases in RSA (Alkon et al, ; Davis et al, ; Hastings, Klimes‐Dougan, Kendziora, Brand, & Zahn‐Waxler, ; Quigley & Stifter, ), which contrasts with patterns observed during naturalistic inductions (like an impossible or frustrating task), which often elicit physiological arousal (Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, ; Hastings et al, ; Perry, Calkins, Nelson, Leerkes, & Marcovitch, ). Using measures of RSA across four emotion contexts, Gaztke‐Kopp and Ram () showed that emotion context‐level physiological change explained a small but unique proportion of the variance in children's RSA scores.…”
Section: Temporally Moderate Contexts Of the Psychobiology Of Self‐rementioning
confidence: 99%
“…The Family Nurture Intervention, a psychosocial intervention based on Calming Cycle Theory that promotes mother‐infant emotional connection through direct interpersonal communication of affect (Welch, ) has also shown promise in preterm infants, with benefits for VVC regulation, socioemotional function, and neurodevelopmental outcomes (Porges et al, in press; Welch et al, ). Interventions focused on parent–child interactions may also improve autonomic function in older children (e.g., Hastings et al, ). In sum, these interventions support social autonomic state regulation as a treatment target.…”
Section: An Autonomic State Regulation Perspective On Treatment and Pmentioning
confidence: 99%
“…In one study, children living in Romanian orphanages with access to physical needs but lacking in emotional caregiver connection exhibited low parasympathetic activity and less flexibility in response to challenges, but those who were randomized into foster care that provided greater emotional interpersonal connection developed autonomic activity much like their peers who had never been institutionalized (34). In a recent study of children referred to Child Protective Services for maltreatment, children developed better parasympathetic flexibility in response to challenges when their caregivers were randomized into a parenting sensitivity intervention compared to peers in a control condition (35).…”
Section: Introductionmentioning
confidence: 99%